Testimony of a father. Or why I wanted my son to join a scout group (Journal of Parents and Teachers, 2017)
Living the experience of scouting is something that deeply marks people, so I wanted my son to join a scout group, an invitation to live a genuine experience of his own. As parents it was also a pedagogical commitment for the future of our children.
Keywords: scouting; personal experience; values; pedagogy